Repair cost-limit replacement policies with minimal repairs - Mohlala, Tshwari Phineas (My University, 2008)
This dissertation examines a number of maintenance models that are implemented to reduce incidences of system failures or to return a failed system to the operating state. In particular, the repair cost-limit (RCL) replacement models are investigated. On failure the system is replaced by an equivalent new one if the random repair costs C exceeds a given repair cost limit c , or at age t by a preventive replacement if in the time interval 0,t no failure induced a replacement of the system. Otherwise, after failure a minimal repair is carried out. After any replacement, the time is returned to zero. For instance, in everyday life, one has to make such decisions once in a while: repair or replace a car, a television set or a refrigerator, depending on the cost of a repair. If the cost of repair is high, then it is more economical to replace the item by a new one. This dissertation considers the combination of the RCL replacement policy with the age replacement policy. An expression for the expected long run cost per unit time (maintenance cost rate) is derived. The optimum values of c and t are obtained.